Research hotspots and trends in pediatric telemedicine: a CiteSpace-based bibliometric analysis (1978–2025) - Xie, Hong; Luo, Dan; Kang, Bingyao (Frontiers in Pediatrics, 2025)
AimGiven the rapid growth yet fragmented nature of pediatric telemedicine research, this study employed bibliometric analysis to address specific research questions regarding key publications, leading authors, core journals, prominent institutions, thematic structures, and research theme evolution. The findings were aimed at providing an objective, panoramic view to guide future research priorities and clinical practice development in pediatric telemedicine.MethodsA retrospective bibliometric analysis was conducted on publications in the field of telemedicine in pediatrics, covering the time period from 1978 to 2025. The data were downloaded from the Web of Science Core Collection on March 4, 2025. This study analyzed the annual number of publications and citations, explored relationships between authors, institutions, countries, and keywords, and identified emerging trends and research frontiers in the field of telemedicine in pediatrics.ResultsA total of 114 countries and 120 institutions published articles on pediatric telemedicine. Co-occurring keywords and cluster analysis indicate that recent major research trends in the field of pediatric telemedicine include telepsychiatry for mental health, autism spectrum disorders, and parent training, as well as digital health for care, service, and quality of life. Additionally, tele-diagnosis and care of, obesity, retinopathy of prematurity, critical care, and traumatic brain injury are also popular research areas.ConclusionThe United States has a significant presence in the field of pediatric telemedicine. Although telemedicine is growing rapidly in pediatrics, it cannot replace face-to-face care.